El maltrato infantil y su incidencia en el desarrollo emocional de los niños y niñas del centro de educación inicial nivel 2 “Geofre Luzuriaga” del cantón Macará, provincia de Loja. período académico 2014-2015”. Lineamientos alternativos - Contento Azuero, Irene Carolina (2016)
This thesis refers to: “EL MALTRATO INFANTIL Y SU INCIDENCIA EN EL DESARROLLO EMOCIONAL DE LOS NIÑOS Y NIÑAS DEL CENTRO DE EDUCACIÓN INICIAL NIVEL 2 “GEOFRE LUZURIAGA” DEL CANTÓN MACARÁ, PROVINCIA DE LOJA. PERÍODO ACADÉMICO 2014-2015”. LINEAMIENTOS ALTERNATIVOS. The same that it was developed according to the Regulation of Academic System of National University of Loja. The central problem of the research work was: ¿How child abuse affects emotional development in children Early Education Center Level 2 "Geofre Luzuriaga" Macará Cantón province of Loja? The overall objective: To sensitize parents on "Child Abuse and its impact on the emotional development of children Initial Level 2". The methods used for the preparation of this research were: Scientific, inductive, deductive, analytic-synthetic, Descriptive and Statistical Model, the same that served effectively help to achieve the proposed research. The techniques and instruments used were: Survey parents was used to identify the types of child abuse that children suffer, Test drawing the human figure that was applied to children to assess the emotional development. According to the results it is concluded that: 66% of parents surveyed think that children are victims of physical abuse during childhood, 28% say they are victims of emotional abuse, factors that influence the emotional development developing child also significantly affect the child's learning and girls. According to the human figure test to assess the emotional development of children 45% is unsatisfactory, 32% very satisfactory, 23% presented a satisfactory emotional development.